Waste sorting campaign for residents of Kelurahan 13 Ulu, Palembang - Rosmiarti Asmar; Kemas Dzaid Ahmad Feedayin; Kiki Tri Nurhayati; Mustika Ayu Dinanti; Neci Ecin; Rahmaisa Lubis; Rahmania Sandika Rega; Reni Apriyanti; Restia Nora Susteny; Romida Awaliya; Suci Tanzila (Community Empowerment, 2024)
The waste problem has become a serious global issue, including in Indonesia. Littering not only damages the environment but also poses a threat to public health. One effective solution to address the waste problem is to increase public awareness of the importance of waste sorting. This community service activity aimed to enhance the understanding of the community of Kelurahan 13 Ulu Palembang regarding the importance of sorting organic and inorganic waste. Through a participatory approach, socialization activities and direct demonstrations of waste sorting were conducted for the community. The results of this activity demonstrated a significant increase in community understanding of the importance of waste sorting. The community was able to differentiate between organic and inorganic waste and implement waste sorting in their daily lives. In addition, this activity also succeeded in increasing public awareness of the benefits of waste sorting, such as compost production and crafts made from fruit baskets, which can provide economic opportunities through recycling.